Vprašanje razvojnega modela Univerze na Primorskem - mestna univerza ali kampus? - Bugarič, Boštjan (Annales. Series historia et sociologia, 2009)
Placing university contents into urban areas improves the quality of living and contributes to the offer of urban contents. Along with changes in city regulation and the regulation of urban development, university contents are a key factor determining the social development of a city. The development of the university inside a city can be divided into two concepts - the first has its roots in Europe and the second in America. The distinctive difference between the two concepts is spatial planningČ the European one advocates university development in close connection with the city, whereas the American one supports a system of autonomous development that is physically separated from the city. The characteristic trend of moving commercial activities from central areas to shopping centres in the suburbs additionally contributes to the reduction of activities in city centres. With an increased number of users living in the centre, the offer as well as the use of the contents in the historic centre would likely be increased. The student population brings a certain financial input and a long-term contribution to generating various events. Remoteness from the place of residence greatly influences the development and use of social contents in the city centre of Koper. Residents not living in the city centre tend to use its contents to a lesser degree. Placing the campus into the suburbs would, due to increased remoteness, negatively affect the implementation of events and lead to a reduction in the number of visitors to the city centre. In such a development scenario, the buildings in the historic centre are likely to remain unused. The remoteness of the campus from the city centre weakens their shared topical connections.
Keywords: Koper; mestno jedro; reurbanizacija; univerze; urbanistično planiranje